ЦАХИМ АРДЧИЛАЛЫН АСУУДАЛД - Д. Бумдарь; Б.ДӨЛГӨӨН (Politology, 2023)
Electronic democracy is an important theme which social informatics must research next to electronic capitalism. The purpose of this paper is along with this line, to address research tasks on decision, deliberation and information in electronic democracy from a decision scientific standpoint.